Pricing Options Embedded in Corporate Bonds Using the Binomial Method - Liu, Qi (Econometric research in finance : ERFIN, 2023)
It is common for a corporate bond to include a call provision that gives the issuing company an option to call, or redeem, the bond at some prespecified set of call prices before the stated maturity date. Since the option is embedded in the bond, it is not traded publicly and thus its value is unknown to bondholders. This study is aimed to price these embedded options and their related bonds, both callable and noncallable, using the binomial method such that the method is set up to approximate the evolution of the short rate. Using reasonable values for the relevant factors and parameters, our results show that the prices of the options and the two types of bonds are noticeably affected by such factors and parameters as the maturity of the bonds, the coupon, the call price, the volatility of the short rate, and the initial short rate.